Genome-Wide Association and Genomic Prediction for Stripe Rust Resistance in Synthetic-Derived Wheats - Mahmood, Zahid; Ali, Mohsin; Mirza, Javed Iqbal; Fayyaz, Muhammad; Majeed, Khawar; Naeem, Muhammad Kashif; Aziz, Abdul; Trethowan, Richard; Ogbonnaya, Francis Chuks; Poland, Jesse; Quraishi, Umar Masood; Hickey, Lee Thomas; et al. (Frontiers in Plant Science, 2022)
Stripe rust caused by Puccnina striiformis (Pst) is an economically important disease attacking wheat all over the world. Identifying and deploying new genes for Pst resistance is an economical and long-term strategy for controlling Pst. A genome-wide association study (GWAS) using SNPs and functional haplotypes were used to identify loci associated with stripe rust resistance in synthetic-derived (SYN-DER) wheats in four environments. In total, 92 quantitative trait nucleotides (QTNs) distributed over 65 different loci were associated with resistance to Pst at seedling and adult plant stages. Nine additional loci were discovered by linkage disequilibrium-based haplotype-GWAS approach. The durable rust resistance gene Lr34/Yr18 provided resistance in all four environments against all five Pst races used in this study. Analysis identified that several SYN-DER accessions that carried major genes: either Yr24/Yr26 or Yr32. New loci were also identified on chr2B, chr5B and chr7D, and 14 QTNs and 3 haplotypes identified on the D-genome possibly carry new alleles of known genes contributed by the Ae. tauschii founders. We also evaluated eleven different models for genomic prediction of Pst resistance, and prediction accuracy up to 0.85 was achieved for adult plant resistance (APR). A meta-analysis based on the large number of existing GWAS would enhance identification of new genes and loci for stripe rust resistance in wheat. The genetic framework elucidated here for stripe rust resistance in SYN-DER identified novel loci for resistance to Pst assembled in adapted genetic backgrounds.